LA NUEVA GESTIÓN PÚBLICA Y SU INCIDENCIA EN LA MUNICIPALIZACIÓN DE LA EDUCACIÓN PERUANA - Bustamante Sánchez de Trujillo, Yolanda (2007)
It is possible to improve the Peruvian Education and for it is necessary to build a new attitude toward the education in order to open space to a new commitment that allows a humanist, integral development that it is centered in the full realization of people. It is necessary a continuous learning in the mark of the New Public Administration that promotes the decentralization of the public services, the citizen participation, the efficiency of the services of the State: Education with the transferring of powers, responsibilities to the local agents: Municipalities and the control of the educational service